2013
DOI: 10.1088/0256-307x/30/6/060303
|View full text |Cite
|
Sign up to set email alerts
|

Collective Excitations of a Dipolar Bose—Einstein Condensate in an Anharmonic Trap

Abstract: The collective excitations of a one-dimensional dipolar Bose-Einstein condensate trapped in an anharmonic potential are investigated theoretically. Using the variational approach, we obtain the coupled equations of motion for the center-of-mass coordinate of the condensate and its width. In particular, analytical expressions for the low-lying excitation modes are given. The results show that dipole-dipole interactions reduce the frequency shift induced by quartic distortion. The interplay between dipole-dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Before the realization of the SO coupled BECs, the influence of weakly deviated pure harmonic potential (hereafter called anharmonicity) on the properties of condensates (both the ground state [13,[23][24][25][26][27][28][29][30][31][32] and the dynamic properties [22,[33][34][35][36][37][38][39][40][41][42][43]) has been extensively studied, and it is found that the anharmonicity of trapping potential affects one-component condensates [26-29, 33-37, 39, 40], dipolar condensates [38] and rotating condensates [23,24,30]. For one-component condensates, the anharmonicity not only makes condensates with a positive scattering length become metastable condensates [44], but also modifies the frequency of collective oscillations such as dipole and breathing modes [33-35, 37, 39, 40, 45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the realization of the SO coupled BECs, the influence of weakly deviated pure harmonic potential (hereafter called anharmonicity) on the properties of condensates (both the ground state [13,[23][24][25][26][27][28][29][30][31][32] and the dynamic properties [22,[33][34][35][36][37][38][39][40][41][42][43]) has been extensively studied, and it is found that the anharmonicity of trapping potential affects one-component condensates [26-29, 33-37, 39, 40], dipolar condensates [38] and rotating condensates [23,24,30]. For one-component condensates, the anharmonicity not only makes condensates with a positive scattering length become metastable condensates [44], but also modifies the frequency of collective oscillations such as dipole and breathing modes [33-35, 37, 39, 40, 45].…”
Section: Introductionmentioning
confidence: 99%
“…For rotating condensates, the anharmonicity allows one to increase the rotation frequency of the condensates above the trap frequency [23], and the resulting change in the ground state phase diagram of the rotating condensates is obtained [24]. For dipolar condensates, the collapse and revival of the collective excitation of condensates can be affected by dipole-dipole interactions and anharmonic distortion [38]. For the thermodynamic properties of condensates, the specific heat, transition temperature and condensation fraction of interacting Bose gases are also modified by anharmonic potential [27].…”
Section: Introductionmentioning
confidence: 99%
“…Within the precise underlying Gross-Pitaevskii (GP) framework, the dynamics of a BEC in an anharmonic potential was studied explicitly in [29,30]. Indeed, the oscillation modes of a 1D BEC trapped in anharmonic potential were discussed with a system of twobody interaction [31,32], two-body and three-body interaction at a low temperature [33,34], as well as for finite temperature [35], and dipolar Bose gas in [36][37][38][39]. The oscillation modes of a 3D BEC in an anharmonic trap were studied in [40].…”
Section: Introductionmentioning
confidence: 99%